2017
DOI: 10.1140/epjc/s10052-017-5152-7
|View full text |Cite
|
Sign up to set email alerts
|

Innermost stable circular orbit of Kerr-MOG black hole

Abstract: We study the innermost stable circular orbit (ISCO) of the metric of the Kerr black hole in modified gravity (Kerr-MOG black hole), which is one of the exact solutions of the field equation of modified gravity in the strong gravity regime. The Kerr-MOG metric is constructed; it is the commonly known Kerr metric in Boyer-Lindquist coordinates by adding a repulsive term like the Yukawa force, which is explained in quantum gravity. In this paper, we numerically calculate the circular orbit of a photon and the ISC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…So it is of great interest to investigate the properties of the black hole in this gravity theory. Many studies demonstrated that there exist distinct differences between this MOG and GR [54][55][56][57][58][59][60][61][62][63][64][65]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…So it is of great interest to investigate the properties of the black hole in this gravity theory. Many studies demonstrated that there exist distinct differences between this MOG and GR [54][55][56][57][58][59][60][61][62][63][64][65]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The static and rotating solutions of MOG were obtained in Ref. [34] and followed by research works examining various aspects of these black holes [33,[35][36][37][38][39][40][41][42]. The particular case of rotating black holes known as Kerr-MOG black holes have gained more astrophysical interests since the observed black holes are thought to be rotating.…”
Section: Introductionmentioning
confidence: 99%
“…The particular case of rotating black holes known as Kerr-MOG black holes have gained more astrophysical interests since the observed black holes are thought to be rotating. For example, the particle dynamics [40], the innermost stable circle orbit [39], the accretion disks [33] and the relativistic jets [38] have been studied. Furthermore, the shadows cast by MOG black holes have been studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The quasinormal modes in the ringdown phase of the merging of two Schwarzschild-MOG black holes has been investigated [11]. Other physical features of the MOG black holes and neutron stars have been investigated [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. As an alternative gravity theory MOG has been shown to agree with data for galaxy rotation curves, galaxy dynamics and cosmology without dark matter [30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%